Oppression and resistance of racialized migrant farmworkers in the context of agricultural racial capitalism : the case of west african farmworkers in the province of Foggia (Italy) - (:unkn) unknown (Università della Calabria, 2024)
The present dissertation intends contributing to the rich debate investigating migrant labor exploitation and resistance in the context of industrial agriculture by looking at the issue through the theoretical perspective of racial capitalism. Adopting this theoretical perspective appears to be fruitful in order to better frame the experience of oppression and resistance of racialized migrant farmworkers. Indeed, while labor studies have often tended adopting a race-blind approach, considering migrant workers as a homogeneous category and race merely as a tool of class division, building on the contribution of theorists of racial capitalism allows to better frame the experience of racialized migrant farmworkers in the context of industrial agriculture, looking at the racial-colonial oppression not as a mere element of the superstructure but rather as integral to the oppression of workers in the context of capitalism. Building on four-years of research developed adopting a militant ethnographic approach informed by decolonial methodologies, the dissertation focuses on exploring the experience of West African migrant farmworkers living in rural informal settlements situated in the province of Foggia. The analysis highlights how the oppression experienced by West African migrant farmworkers in the province of Foggia can be explored as being at the intersection of four processes: ghettoization, exploitation, illegalization and racialization. These processes appear to be central both in defining their experience of oppression and in motivating their struggle for liberation. In addition, the ambivalent role of NGOs operating in the area is explored, as representing an integral element to the reproduction of systems of oppression through policies aimed at preventing racialized migrant farmworkers fully achieving their right to self-determination, while at the same time avoiding conflict with institutions. Nevertheless, despite the increasing <NGO-ization of resistance=, particularly pronounced in the province of Foggia, West African migrant farmworkers have been the protagonists of multiple forms of resistance and mobilization in the province of Foggia in the past few years, proving their determination to struggle for the recognition of their rights.
Dottorato di Ricerca in Politica, Cultura e Sviluppo. Ciclo XXXVI
Keywords: Migrazioni; Agricoltura; Sfruttamento; Sindacalizzazione; Capitalismo razziale